2006
DOI: 10.1348/014466605x53596
|View full text |Cite
|
Sign up to set email alerts
|

Constructing identities in cyberspace: The case of eating disorders

Abstract: This paper consists of a discourse analysis of data collected from websites that have been created by and for people who wish to share experiences of eating disorders in a positive and supportive environment. These sites have earned the broad description 'pro-ana' (where 'ana' is short for 'anorexia'). Site users have come to see themselves as a broad on-line community of like-minded individuals, but within this community there are many subgroups, and the boundaries between these subgroups are fiercely contest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 22 publications
5
152
3
6
Order By: Relevance
“…As Giles (2006) highlighted in relation to pro-ana sites, considerable effort is expended in striving for the right to call oneself 'ana' and to distance oneself from devalued outgroups such as 'wannabes'. We also found that the recovery site focused on the 'person inside' and being 'mentally healthy' as a means of demonstrating their right to membership of the 'in-group'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Giles (2006) highlighted in relation to pro-ana sites, considerable effort is expended in striving for the right to call oneself 'ana' and to distance oneself from devalued outgroups such as 'wannabes'. We also found that the recovery site focused on the 'person inside' and being 'mentally healthy' as a means of demonstrating their right to membership of the 'in-group'.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding patterns of talk on these different sites can inform our understanding of their differences and similarities. Previous work has suggested that talk on recovery and pro-ana sites may not reflect their apparent oppositional ideologies (Giles, 2006;Wilson et al, 2006). In this paper we examine body-talk on one pro-ana and one recovery web site to explore this contradiction, and specifically to discover how identities associated with weight and body management are negotiated, managed and developed within the context of online eating 'disorder' related self help/lifestyle websites.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies focus on gender (e.g., Charlebois, 2010;Potter and Edwards, 2003;Stokoe, 2012;Schegloff, 1997;Rhodes and Pullen, 2009), identity (e.g., Benwell and Stokoe, 2012;Locke and Edwards, 2003;Myers, 2010;Condor, 2000;Hobbs, 2003;Ainsworth and Hardy, 2004;Abell and Stokoe, 2001;Davies and Harré, 1990;Crane, 2012b;Rautajoki, 2012;Holmes, 2005;Bucholtz and Hall, 2005;Mieroop, 2005;Brown and Phua, 2011;Wetherell, 2001;Greatbatch, 2009;Gulich, 2003;Giles, 2006;Hutchby, 2001;Whittle, 2005), attitudes and evaluative practices (e.g., Wiggins and Potter, 2003;Potter, 1998a;Potter and Edwards, 2012), occupational roles and good practice (e.g., Marshall, 1994;Wasson, 2004;Svennevig, 2012b;Ford and Stickle, 2012;Housley and Smith, 2011;Nielsen, 2012;Holmes, 2005;Cromdal, Landqvist and Osvaldsson, 2012), and knowing as an interactional accomplishment (Lester and Paulus, 2011;Marra, Moore and Klimczak, 2004;Gulich;Paulus, 2007;…”
Section: Topics Of Study In Discourse Analysismentioning
confidence: 99%
“…Research in CMC tends to be clustered around academic sites (e.g., McKenzie and Murphy, 2000;Montero Watts and Garcia-Carbonnell , 2007;Marra, Moore and Klimczak, 2004;Lester and Paulus, 2011;Schrire, 2006;Paulus, 2007;Veerman and Veldhuis-Diermanse, 2001;Jordan, Schallert, Park, Lee, Chaing and Cheng, 2012); online support groups for people with physical or mental health issues such as eating disorders (e.g., Stommel and Koole, 2010;Giles, 2006), self-harming (e.g., Smithson, Sharkey, Hewis, Jones, Emmens, Ford and Owens 2011) and depression (e.g., Morrow, 2006;Chirrey, 2011); and blogs (e.g., Myers, 2010). Appearing less frequently as a focus of research are sites such as product review sites (e.g., Otterbacher, 2011) and professional practice forums (e.g., Crane, 2011;.…”
Section: Coveragementioning
confidence: 99%